The Effect of ESG Controversy on Firm Value in Southeast Asia with Analyst Coverage As A Moderating Variable - Abady, Adylah; Raudhatul Hidayah (Universitas Muhammadiyah Surakarta, 2025)
This study examines the impact of ESG (Environmental, Social, and Governance) controversies on firm value in Southeast Asia, with analyst coverage as a moderating variable. Using 1,255 observations from non-financial public companies listed on Southeast Asian stock exchanges during 2019–2023, the study employs quantitative methods with data from Refinitiv Eikon. Results show that ESG controversies negatively and significantly affect firm value, as measured by Tobin’s Q and Market Capitalization. Companies involved in ESG controversies experience reduced market value. Analyst coverage does not significantly moderate this relationship, although during the COVID-19 pandemic, it better mitigated the negative impact on Tobin’s Q, likely due to heightened investor demand for strategic information. Findings indicate that investor sensitivity to analyst coverage varies with firm value metrics. Investors are encouraged to critically assess companies' ESG reports and not solely depend on analyst recommendations, especially amid ESG controversies.